Surprising spies : and unexpected heroes of World War II - Ruelle, Karen Gray (Holiday House, 2020)
Contributes accounts of assorted Allied spies during World War II who led public lives, including that of a performer, sports hero, and princess, while acting as informants and housing refugees. Includes photographs and further resources.